2019
DOI: 10.3390/sym11060824
|View full text |Cite
|
Sign up to set email alerts
|

Inference about the Ratio of the Coefficients of Variation of Two Independent Symmetric or Asymmetric Populations

Abstract: Coefficient of variation (CV) is a simple but useful statistical tool to make comparisons about the independent populations in many research areas. In this study, firstly, we proposed the asymptotic distribution for the ratio of the CVs of two separate symmetric or asymmetric populations. Then, we derived the asymptotic confidence interval and test statistic for hypothesis testing about the ratio of the CVs of these populations. Finally, the performance of the introduced approach was studied through simulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…It can happen that γ(θ) = θ j , for some j. Let also (4) H : ϕ = ϕ H be the hypothesis that we want to test by means of the BDM. If it is possible to compute the marginal posterior of ϕ, i.e.…”
Section: Defining the Bayesian Discrepancy Measure And The Related Testmentioning
confidence: 99%
See 1 more Smart Citation
“…It can happen that γ(θ) = θ j , for some j. Let also (4) H : ϕ = ϕ H be the hypothesis that we want to test by means of the BDM. If it is possible to compute the marginal posterior of ϕ, i.e.…”
Section: Defining the Bayesian Discrepancy Measure And The Related Testmentioning
confidence: 99%
“…Usually it is assumed that the data follows symmetric distributions, however asymptotic tests for asymmetric distributions have also been discussed. For instance, the case of the lognormal distribution is considered in [2] and [3], and a most general assumption of asymmetry, with applications to the Beta and the Gamma distributions, has been considered in [4]. Nonparametric techniques, such as bootstrap, which free up the analysis from the parametric restrictive assumptions, have also alternatively been proposed (see [5] and [6]).…”
Section: Introductionmentioning
confidence: 99%
“…The NTP offset measurements were conducted simultaneously with raw offset measurements in the same WAN. To compare the outcomes of such related measurements based on the variability of predicted offsets, a statistical parameter called 'coefficient of variation (CV)' [33] was used. CV is a statistical measure of the relative dispersion of data points in a data series around the mean.…”
Section: All Network Tracesmentioning
confidence: 99%
“…The statistics of papers called for this Special Issue related to published or rejected items were [7][8][9][10][11][12][13][14][15][16][17][18][19][20]: total submissions (21), published (13; 62%), and rejected (8; 38%). The authors' geographical distribution by countries of authors in published papers is shown in Table 1, and it can be seen that 35 authors are from 11 different countries.…”
Section: Statistics Of the Special Issuementioning
confidence: 99%